Investigasi Pengaruh Jarak Celah Sinapsis dengan menggunakan Metode Monte Carlo - Eklesias Donesi Andresta; Nur Aji Wibowo; Adita Sutresno (Jurnal Fisika dan Aplikasinya, 2020)
Neurons in the human brain are interconnected and influence each other. Signal integration in brain is determined by the size and the fast synapses response kinetics. This research aims to study the effect of synaptic cleft distance on signaling through a diffusion process using the Monte Carlo Cell simulation program. This research is important to investigate the diffusion process in the body related to the effect of diffusion on signaling if the cleft, area, and concentration are varied. MCell is a probabilistic simulation which a solution of a problem is given based on the probability calculation process. This study uses modeling 3 spherical compartments representing pre-synapses, post-synapses, and neurons as the outer boundary of synapses and as a cleft between pre-synapses and post-synapses. The simulation results showed that the effect of change in the cleft distance on molecular distribution was 98,86%. The narrower size of the cleft distance causes faster molecular distribution. The broader the receptor area (6;12;18;24) causes the molecules to be distributed to increase ((1661;2173;2249;2264)moles). An increase in the amount of concentration (2000;4000;6000;8000) also makes the diffusion rate faster ((1380;2806.25;4203.75;5565)moles/s). The faster the diffusion rate indicates that the signaling process is getting faster.